(3OQGSI JMdjdjI ebGQfIs - (3CSGeI CMeO(B, (3GdefGYSIs; (3LdGd eMeO GdRYHj(B, (3UGjd aGVd GdghGhTIs ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 2001)
(3GdeOdhd GdYGe dLQGFe GdMGSH GdBdj hGdEfJQfJ(B-(3GdLQGFe GdhGbYI Ydi GdMGSH GdBdj(B-(3GdLQGFe GdeQJcHI HhGSWI GdMGSH GdBdj(B-(3CUhd GdJMbjb Gdafj aj HjFI GdMGSH GdBdjs
(3HHdjhZQGajG(B: (3U(B.303s
Keywords: (3GdLQGFes; (3GdMGSHGJ GdEdcJQhfjIs; (3GdMhGSjHs